Reducing Public Masturbation in Individuals With ASD: An Assessment of Response Interruption Procedures. Issue 3 (May 2020) - Cividini-Motta, Catia; Moore, Keira; Fish, Lauren M.; Priehs, Jonathan C.; Ahearn, William H.
Individuals with autism may engage in sexual behavior at inappropriate times and/or in inappropriate places. The current study investigated the effects of response interruption and redirection (RIRD) and response interruption (RI) on public masturbation (PM) of children and adolescents with autism. Initial assessments showed that PM was maintained by automatic reinforcement. During the treatment evaluation phase, we compared RIRD and RI to determine whether either procedure was successful in decreasing the duration of PM. In the RIRD condition, contingent on the occurrence of any PM the participant completed physical activities involving both hands (e.g., moving chairs, touching toes). In the RI condition, the therapist interrupted all instances of PM using physical and verbal prompts (e.g., saying in a neutral tone, "Stop that" and moving hands away from genitals). Both procedures were effective in decreasing the duration of PM but RI required fewer resources and less time. Clinical implications and suggestions for future research are reviewed.